Importance of blood elastic property in the arterial hemodynamics: a patient specific numerical study - S.I.S. Pinto (2018)
8th World Congress of Biomechanics, Dublin-Ireland, 08-12 July, 2018, Symposium: Patient-specific biomechanical interaction of cardiovascular devices with surrounding tissues. Imaging and Device Biomechanics, organized by Rosaire Mongrain and Eoghan Cunnane, Oxford Abstract No. O1974.